Alternatives to valproate in girls and women of childbearing potential with Idiopathic Generalized Epilepsies: state of the art and guidance for the clinician proposed by the Epilepsy and Gender Commission of the Italian League Against Epilepsy (LICE). (February 2021) - Mostacci, Barbara; Ranzato, Federica; Giuliano, Loretta; La Neve, Angela; Aguglia, Umberto; Bilo, Leonilda; Durante, Vania; Ermio, Caterina; Monti, Giulia; Zambrelli, Elena; Lodi, Monica Anna Maria; Galimberti, Carlo Andrea
Highlights: High quality studies on antiseizure medications in IGEs are lacking. LEV and LTG should be first-choice drugs in GTCS Alone and JME in girls and WOCP. LTG should be first-choice drug in JAE in girls and WOCP. ESM should be first-choice drug in CAE in girls. More data on the efficacy of new ASMs in IGEs and their safety in pregnancy are needed. Abstract: Following recent European Medication Agency restrictions on valproate (VPA) use in girls and women of childbearing potential (WOCP), the Commission on Epilepsy and Gender of the Italian League against Epilepsy integrated current literature and legislative data in order to provide clinicians with guidance on antiseizure medication (ASM) prescription for Idiopathic Generalized Epilepsies (IGEs) in this population, avoiding VPA. We reviewed the updated literature on ASMs and examined the teratogenicity of those showing efficacy in IGEs. For all relevant ASMs, we considered the indications for use and the pregnancy and contraception-related recommendations given in the Italian Summary of Product Characteristics (SmPC) and on the websites of the European Medicines Agency (EMA) and other European Union (EU) countries' regulatory agencies. With the exception of absence seizures, the literature lacks high quality studies on ASMs in IGEs. In girls and WOCP, levetiracetam and lamotrigine should be considered the first-choice drugs in Generalized Tonic-Clonic Seizures Alone and in Juvenile Myoclonic Epilepsy, lamotrigine in Juvenile Absence Epilepsy, and ethosuximide in Childhood Absence Epilepsy. Although supported by the literature, several ASMs are off label, contraindicated or burdened by special warnings in pregnancy. Some discrepancies emerged between the various SmPC warnings for different brands of the same active principle. We provided a therapeutic algorithm for each IGE syndrome and highlighted the need for revised prescription rules, consistent with the latest literature data, uniformity of SmPC warnings for the same active principle, and more data on the efficacy of new ASMs in IGEs and their safety in pregnancy.